STRATEGI PERTUMBUHAN AYU JEGES SALON SEBAGAI UPAYA PENCAPAIAN KEBERLANJUTAN BISNIS DI INDUSTRI KECANTIKAN - Asima Winola Siahaan; Khafi Puddin; Fadli Agus Triansyah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This research aims to analyze the business growth strategy of Ayu Jeges Salon through a market penetration approach as an effort to achieve business sustainability in an increasingly competitive beauty industry. While the beauty industry in Indonesia is experiencing rapid growth, it also faces intense competition between small and medium-sized enterprises (SMEs) and larger, well-capitalized players. This study employs a descriptive qualitative approach with data collection techniques involving in-depth interviews, observation, and documentation studies. Data analysis utilizes SWOT and Ansoff Matrix frameworks to identify the salon's strategic position. The results indicate that Ayu Jeges Salon has great potential to increase its market share through a market penetration strategy, which includes: (1) improving service quality and beauty product innovation, (2) strengthening digital marketing-based promotional strategies, (3) implementing customer loyalty programs, and (4) optimizing competitive pricing. This study concludes that the implementation of an integrated market penetration strategy is capable of driving sustainable business growth and increasing the competitiveness of Ayu Jeges Salon in the local market.